The performance improvement of a lowcost INS/GPS integration system using the street return algorithm - Thang, Nguyen Van; Thang, Pham Manh; Tan, Tran Duc (Vietnam Journal of Mechanics, 2012)
During the last decades, MEMS technology has undergone rapidly development, leading to the successful fabrication of miniaturized mechanical structures integrated with microelectronic components. Accelerometers and gyroscopes are in great demand for specific applications ranging from guidance and stabilization of spacecraft to research on vibrations of Parkinson patient’s fingers. The demand of navigation and guidance has been urgent for many years. In fact, INS is used daily in flight dynamics control. Nowadays, with the strong growth of Microelectromechanical system (MEMS) technology, the Inertial Navigation Systems are applied widely. However, there are existing errors in the accelerometer and gyroscope signals that cause unacceptable drifts. Even when the Inertial Navigation System (INS) was supported by the Global Positioning System (GPS), the position error is still large, especially in the case of GPS signal lost. In this paper, we will present a simple algorithm called Street Return Algorithm (SRA) to reduce this kind of error. Experimental result showed that this algorithm could be applied in the real-time operation.